Studies on the origin of dropwise condensation of steam on ion implanted metallic surfaces [Untersuchungen zur Ursache der Tropfenkondensation von Wasserdampf an ionenimplantierten Metalloberflächen] - Rausch, Michael Heinrich; Durst, Karsten; Göken, Mathias; Jakobs, Peter-Jürgen; Leipertz, Alfred; Fröba, Andreas Paul (Chemie Ingenieur Technik, 2011)
The origin of dropwise condensation of steam on ion implanted metallic surfaces was fundamentally studied. Condensation experiments and surface analyses showed that chemically inhomogeneous surfaces with topographic microstructures are likely to induce dropwise condensation. These surface characteristics are caused by particulate precipitates. Such particles are formed on ion implanted surfaces by the degradation of the material supersaturation with the doping elements. Similar surfaces showing dropwise condensation also emerged spontaneously on several unimplanted, high-alloyed materials due to oxidation and erosion effects induced by the condensation process. For explaining the observed condensation phenomena on the identified surface characteristics, a new model for the condensation mechanism was developed.
WW1::903
Keywords: Condensation; Ion implantation; Metals; Surface technology; Wettability